Detection and differentiation of Leptospira spp. serovars in bovine semen by polymerase chain reaction and restriction fragment length polymorphism - Heinemann, M. B.; Garcia, José Fernando [UNESP]; Nunes, Caris Maroni [UNESP]; Gregori, F.; Higa, ZMM; Vasconcellos, S. A.; Richtzenhain, L. J. (Elsevier B.V., 2000)
In view of the importance of venereal transmission of bovine leptospirosis, the objective of the present study was to apply the polymerase chain reaction (PCR) to 26 serovars of Leptospira interrogans, L. borgpetersenii, L. santarosai, L. noguchii and L. biflexa, to determine the detection threshold in semen samples and to evaluate the possibility of differentiation among serovars using 19 restriction endonucleases. The results showed that all serovars were amplified and the detection threshold in semen samples of a bull was 100 bacteria/ml. Using endonucleases we could classify the 26 serovars into eight groups. The present results show that PCR is a method of great potential for the detection of Leptospira spp, at bovine artificial insemination centers. (C) 2000 Elsevier B.V. B.V. All rights reserved.
Keywords: cattle-bacteria; Leptospira spp.; PCR; RFLP